Data-driven environments: Evaluating IoT sensors and KNX protocol for monitoring indoor conditions in educational facilities - Rus, Tania; Moldovan, Raluca Paula; Mârza, Carmen Maria; Corsiuc, Georgiana; Iluţiu-Varvara, Dana-Adriana (Frontiers in Built Environment, 2025)
Educational institutions face a growing challenge in creating indoor environments that support both student wellbeing and operational efficiency. This case study, conducted within two university classrooms at the Technical University of Cluj-Napoca, Romania, assesses the reliability of a smart building system deployed to monitor indoor parameters. The system, which features integrated wall-mounted Internet of Things (IoT) sensors communicating via the KNX protocol, is evaluated by benchmarking its performance to that of a professional monitor instrument (Testo 400). The methodology involved a mixed-methods approach, combining quantitative data from the KNX-based automation network and Testo 400 monitor with qualitative feedback from occupants on thermal comfort, humidity, and indoor air quality. While a systematic offset was observed, with the professional monitor yielding higher readings, the KNX system demonstrated notable consistency. The statistical analysis revealed a strong Pearson’s correlation (up to 0.98, p < 0.001) for CO2 and relative humidity, followed by temperature (up to 0.97). Despite successful thermal comfort maintenance, indoor air quality emerged as a significant concern due to CO2 levels frequently indicating severe ventilation deficiencies. Comparative analysis showed minimum CO2 concentrations fell into EN 16798–1:2019 Category II/III, while maximum concentrations exceeded both Category IV (Red rating) and the ASHRAE 62.1–2022 threshold. Beyond validating KNX’s reliability for indoor environmental quality monitoring in this specific context, this case study highlights the critical need for ventilation system upgrades in higher education to effectively control high CO2 concentrations and foster healthier learning environments.